Perlindungan Hukum Perdata terhadap Pengguna AI dalam Pengelolaan Data Identitas Masyarakat Berdasarkan Pasal 1367 KUHPerdata - M. Hafidz Novta. D; Ali Azhar; Vivi Arfiani Siregar (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2026)
This study aims to analyze the form of civil legal protection for users of Artificial Intelligence (AI) in managing public identity data under Article 1367 of the Indonesian Civil Code, as well as to examine civil liability for losses arising from the use of AI. This research employs a normative legal method using statutory, conceptual, and case approaches. The study relies on primary, secondary, and tertiary legal materials, which are analyzed qualitatively through a deductive method. The findings indicate that Article 1367 of the Civil Code remains relevant as the legal basis for determining liability arising from the use of AI because AI is legally regarded as an object under human control rather than an independent legal subject. Civil liability is imposed on the party exercising control or benefiting from the AI system according to the applicable legal relationship. Legal protection is further strengthened by the Personal Data Protection Law and the Electronic Information and Transactions Law to ensure legal certainty and safeguard citizens' rights in the digital era.